Pearl Millet (Pennisetum glaucum L.) Research in India: A Scientometric Journey through the Last Two Decades (2000-2022): Pearl millet scientometric journey - Naorem, Anandkumar; M., Saritha; Doodhawal, Kiran; Jaajpera, Tejaswini; Ram, Basta; Kumar, Shrvan; Panwar, N.R.; Meena, K.K. (Annals of Arid Zone, 2023)
Pearl millet (Pennisetum glaucum L.), a member of the Poaceae family, is a widely cultivated cereal crop and considered to be one of the most important millet crops globally due to its remarkable drought tolerance, adaptability to marginal environments, and high nutritional value. This scientometric study aims to identify the most relevant sources of information in the field of pearl millet research in India during 2000-2022. A total of 844 documents from 181 sources were identified, indicating a moderate level of research activity. The average citations per document were 13.42, suggesting that the research landscape in India has received a reasonable level of attention in the scientific community. The highest number of articles published were in 2021 (55) followed by 2020 (51) and 2018 (44). The data showed that the Indian Journal of Agricultural Sciences was the most prolific and the other journals maintained a relatively stable production over time. The most frequent topics were downy mildew, Sclerospora graminicola, and sorghum. The results suggest that India has established collaborative relationships with various countries worldwide to produce scientific papers.